1995
DOI: 10.1111/j.1439-0329.1995.tb01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Fungi colonizing Scots‐pine cone scales and seeds and their pathogenicity

Abstract: Fungi were isolated from the cone seales and seeds of Scots pine using plating on malt-extraet agar and/or the standard blotter method in a Jaeobsen's apparatus.Alternaria alternata, Epicoccum purpurascens and (jlocladium atrum were isolated from dampingoff seedlings germinating on agar or filter paper, but, in pathogenieity tests with peat-sand (1 :3) growth substrate, they were not pathogenic. All the Fusarium species isolated were pathogenic in growth substrate. Some E. avenaceum colonies formed no aerial h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Several fungi damage cones, kill seeds or attack seedlings at germination (CALLAN and FUNK 1994). Fungi frequently colonize pine cone scales and seeds (LILJA et al 1995). UROSEVIC (1961) reported that the average number of spores was 50 000^150 000 per gram of seeds in Scots pine (Pinus sylvestris L.) and Norway spruce (Picea abies [L.] Karst.).…”
Section: Introductionmentioning
confidence: 99%
“…Several fungi damage cones, kill seeds or attack seedlings at germination (CALLAN and FUNK 1994). Fungi frequently colonize pine cone scales and seeds (LILJA et al 1995). UROSEVIC (1961) reported that the average number of spores was 50 000^150 000 per gram of seeds in Scots pine (Pinus sylvestris L.) and Norway spruce (Picea abies [L.] Karst.).…”
Section: Introductionmentioning
confidence: 99%
“…Apparently F. subglutinans was the main fungus isolated from Pinus seed in the United States (Dwinell and Fraedrich 1997). On P. sylvestris seed from Finland, F. oxysporum and F. avenaceum were pathogenic in growth substrates (Lilja et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Another typical disease caused by seed-borne fungi is damping-off, in which germinants are infected and die before emergence, or necrosis appears in small seedlings near the ground line (Sutherland et al 2002). Fungi in genera such as Fusarium, Alternaria and Phoma are known to cause damping-off in numerous plant species (Mittal & Wang 1993, Lilja et al 1995, Salerno & Lori 2007. Root rot is often caused by similar fungi, but in the last decade it has seldom caused problems in Finnish nurseries due to changes is seedling production practices and nursery hygiene.…”
Section: Seed-borne Microbes and Their Control During Seed Handling Amentioning
confidence: 99%